Cognitive FH Channel Selection for Bluetooth Network - Yi Peng; Qingzhi Du; Long Hua; Yubing Shao (Institute of Advanced Engineering and Science, 2013)
Bluetooth is a short-range wireless technology that operates in the 2.4GHz unlicensed ISM band, so it will inevitably encounter the interference from other wireless systems and other Bluetooth piconets. Because of the flexible, efficient and reliable spectrum access by adapting the radio’s operating characteristics to the real-time conditions of the environment, cognitive radio technology is apply in Bluetooth network. In this paper, a novel cognitive FH channel selection method which is built based on link quality detection is proposed, interference temperature judgments model is analyzed and cognitive processing cycle of channel access is discussed. The simulation results indicated that cognitive FH Bluetooth network is more anti-interference than conventional Bluetooth systems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2317